A novel robust scene change detection algorithm for autonomous robots using mixtures of gaussians - Manso, Luis (2015)
Submitted by Eliezer Mendes Lopes (mendesfurg@gmail.com) on 2015-04-08T17:03:12Z No. of bitstreams: 1 A Novel Robust Scene Change.pdf: 2647017 bytes, checksum: 9c1a51777cf6188361de1c300d6bb0ec (MD5)